Discovery and re-description of Tetranychus taiwanicus Ehara (Acari: Tetranychidae) from citrus in India. Issue 4 (4th July 2018) - Kowsika, S.; Ramaraju, K.; Jeyarani, S.; Mohan Kumar, S.
ABSTRACT: Tetranychus taiwanicus is recorded for the first time in the Indian sub-continent from Citrus sp. and re-described in detail here. Tetranychus taiwanicus and its putative close relative Tetranychus fijiensis Hirst, 1924 are unusual members of Tetranychus, being differentiated from the other Tetranychus species by the presence of empodia with two pairs of proximoventral hairs, the dorsal being much smaller than the ventral, and males with a large, elongate, tapering aedeagus. Tetranychus taiwanicus is most easily distinguished from T. fijiensis by its substantially smaller, thicker aedeagus.